The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1590/s0034-89102010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns in early childhood and the onset of menarche before age twelve

Abstract: OBJECTIVE:To examine the relationship between growth patterns in early childhood and the onset of menarche before age 12. METHODS:The study included 2,083 women from a birth cohort study conducted in the city of Pelotas, Southern Brazil, starting in 1982. Anthropometric, behavioral, and pregnancy-related variables were collected through home interviews. Statistical analyses were performed using Pearson's chi-square and chi-square test for linear trends. A multivariable analysis was carried out using Poisson re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
(49 reference statements)
1
8
0
2
Order By: Relevance
“…The inclusion of weight gain in the model of predictors of menarche and first ovulation is consistent with a long-standing literature that accelerated prepubertal growth contributes significantly to an earlier onset of puberty (Frisch, 1984; Mesa et al, 2010; Tanner and Whitehouse, 1975; Wehkalampi et al, 2011). Weight gain is a surrogate measure of a number of variables, including the balance between food intake and energy expenditure; stress-induced inhibition of growth signals (Coplan et al, 2000); neuroendocrine signals that stimulate lean and bone mass; and signals from accumulating fat mass.…”
Section: Discussionsupporting
confidence: 85%
“…The inclusion of weight gain in the model of predictors of menarche and first ovulation is consistent with a long-standing literature that accelerated prepubertal growth contributes significantly to an earlier onset of puberty (Frisch, 1984; Mesa et al, 2010; Tanner and Whitehouse, 1975; Wehkalampi et al, 2011). Weight gain is a surrogate measure of a number of variables, including the balance between food intake and energy expenditure; stress-induced inhibition of growth signals (Coplan et al, 2000); neuroendocrine signals that stimulate lean and bone mass; and signals from accumulating fat mass.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that the most obese girls tend to reach menarche at an earlier age than do their normoweight counterparts [45][46][47][48]. The association with height in childhood is less conclusive, though it has been shown that girls who underwent more accelerated growth in their childhood also experienced earlier menarche [24,49,50]. In our study, we also observed that girls who were slightly taller or much taller than the average in their prepubertal stage underwent menarche earlier than the shortest girls (12.6 vs. 13.0 years, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Schraiber et al, conducted a study with the objective of validating the instrument, World Health Organization Violence against Women (WHO VAW) on psychological, physical and sexual violence by intimate partners against women 10 . Authors translated, adapted and validated the content of the Childhood Trauma Questionnaire , which is administered to adolescents and adults, with the aim to investigate the history of abuse and neglect during childhood 11 . …”
Section: Discussionmentioning
confidence: 99%
“…However, effective tools to assess this knowledge are not available. Although tools for evaluation of the victims of psychological, physical and sexual violence are available, instruments aiming to evaluate health professionals were not found 10 - 11 . Further studies are necessary to verify the knowledge of professionals that guide public health policies, and to combat domestic violence in children.…”
Section: Introductionmentioning
confidence: 99%